2012
DOI: 10.1508/cytologia.77.97
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid Genome Structure of <i>Drosera spatulata</i> Complex (Droseraceae)

Abstract: SummaryTo infer genome structures and chromosome differentiations with karyomorphological changing among these 3 Drosera species, we applied base-specific fluorescent staining with GC-rich specific chromomycin A 3 (CMA) and AT-rich specific 4′,6-diamidino-2-phenylindole (DAPI), fluorescent in situ hybridization (FISH) with 45S rDNA, and genomic in situ hybridization (GISH) with 2 parental genomic probes of D. rotundifolia (2n=20)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The highest percentage of similarity between D. rotundifolia and D. tokaiensis seems to show a close relationship among the three species. However, previous molecular and cytogenetic works clearly demonstrated that D. tokaiensis was an allopolyploid (2n=6x= 60, hexaploid) with hybrid origin between D. rotundifolia (2n=2x=20, diploid) as the paternal ancestor and D. spatulata (2n=4x= 40, tetraploid) as the maternal ancestor (Hoshi et al 2008, Hoshi et al 2010, Shirakawa et al 2012.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The highest percentage of similarity between D. rotundifolia and D. tokaiensis seems to show a close relationship among the three species. However, previous molecular and cytogenetic works clearly demonstrated that D. tokaiensis was an allopolyploid (2n=6x= 60, hexaploid) with hybrid origin between D. rotundifolia (2n=2x=20, diploid) as the paternal ancestor and D. spatulata (2n=4x= 40, tetraploid) as the maternal ancestor (Hoshi et al 2008, Hoshi et al 2010, Shirakawa et al 2012.…”
Section: Resultsmentioning
confidence: 96%
“…In Japan, this species occurs in the main Islands except the Ryukyu Islands (Horikawa 1976, Nakano et al 2004. The leaves of the species are spoon-shaped (Nakano et al 2004, Shirakawa et al 2012, Hoyo and Tsuyuzaki 2013, and all plants are the diploid with middle size (2-3 µm) of metaphase chromosomes (2n=2x=20M) (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After about 10 d, the primary roots growing straight were collected and treated with 0.05% colchicine for 10 h, fixed in a fixative mixed with ethanol-acetic acid-chloroform (2 : 1 : 1) and then stored in a deep freezer until use. Fluorescent banding using CMA and 4′,6-diamidino-2-phenylindole (DAPI) was adapted to plant chromosomes by Schweizer (1976) and is effective for karyotype analysis in other various plant species (Hoshi et al 2008, Urdampilleta et al 2008, Zaman and Alam 2009, Begum et al 2010, Fawzia and Alam 2011, Hoshi et al 2011, Shahla and Alam 2011, Shirakawa et al 2012, Kuroki et al 2013. The fluorescent banding procedure simplified and adapted for conifer chromosome analysis by Kondo and Hizume (1982) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) has been useful to detect DNA distribution in nuclei and on chromosomes (Hoshi et al 2011, Shibata and Hizume 2011, Ebadi-Almas et al 2012, Shirakawa et al 2012, Suto et al 2012, Ikeda et al 2013, Kuroki et al 2013, Ruan et al 2013, Yokomi et al 2013, Suto et al 2013, Lombello and Pinto-Maglio 2014, Abo-Zeid et al 2015, Kantek et al 2015, Shibata and Hizume 2015, Matsunaga 2016). However, FISH supplies only a snapshot of subnuclear dynamics because it requires the fixation of cells and DNA denaturation with high temperature for hybridization.…”
mentioning
confidence: 99%